1998
DOI: 10.1136/bmj.316.7127.262
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and acceptability of antenatal HIV testing: randomised controlled trial of different methods of offering the test

Abstract: Objective: To determine the uptake and acceptability of different methods of a universal offer of voluntary HIV testing to pregnant women. Design: Randomised controlled trial involving four combinations of written and verbal communication, followed by the direct offer of a test. The control group received no information and no direct offer of a test, although testing was available on request. Setting: Hospital antenatal clinic covering most of the population of the city of Edinburgh. Subjects: 3024 pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 23 publications
0
112
2
1
Order By: Relevance
“…Many studies have demonstrated missed opportunities for earlier HIV diagnosis [33][34][35]. Others have identified strategies to improve uptake of HIV testing [36][37][38]. 'UK National Guidelines for HIV Testing 2008' were introduced with the aim of increasing HIV testing in a wider range of healthcare settings and reducing the number of patients diagnosed late with HIV [39].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated missed opportunities for earlier HIV diagnosis [33][34][35]. Others have identified strategies to improve uptake of HIV testing [36][37][38]. 'UK National Guidelines for HIV Testing 2008' were introduced with the aim of increasing HIV testing in a wider range of healthcare settings and reducing the number of patients diagnosed late with HIV [39].…”
Section: Discussionmentioning
confidence: 99%
“…The first challenge is the most urgent and basic, as health professionals represent a key factor in screening. In fact, the choice of whether to have a screening test performed is greatly influenced by the personal attitude of the health professionals offering the screening (245). In addition, health professionals who have limited knowledge and thus are unable to inform patients may ultimately affect the choice (248).…”
Section: Universal Serology Screeningmentioning
confidence: 99%
“…Down syndrome), the neonate 111 (e.g. congenital hearing impairment) or the mother, which may also affect the baby 112 (e.g. HIV status).…”
Section: Introductionmentioning
confidence: 99%